Progress in the Development of a Double Stub Tuner for Alcator C-Mod Lower Hybrid Current Drive System. (3rd October 2017) - Koert, P.; Terry, D.; Fitzgerald, E.; Wukitch, S.
Abstract: This technical note describes the ongoing development of a double stub Fast Ferrite Tuner (FFT) for the Alcator C-Mod 4.6 GHz Lower Hybrid Current Drive (LHCD) system. This FFT uses an electromagnet coil and permanent magnet on each tuning stub. The FFT is required to withstand over 200 kW of power (20 KW/cm 2 ) for several second pulses spaced 10 minutes apart. The FFT will be computer controlled and must react to matching a load in a few hundred microseconds. We will present measurement of the system along with simulations. Breakdown measurements, operational achievements and computer control algorithm will be shown. This program has also revealed the inaccuracy in simulation of the models in leading finite element codes such as CST and COMSOL. We have been able to insert a model for Ion Cyclotron Range of Frequency (ICRF) work into COMSOL but unable to do this for Lower Hybrid at this time.